Leaf Blight and Purple Seed Stain caused by Cercospora kikuchii in soybean (Glycine max L. Merr.) - Lavilla, M.; Ivancovich, A.; Díaz-Paleo, A. (Agronomía Mesoamericana, 2022)
Introduction. Cercospora Leaf blight and Purple Seed Stain are diseases caused by Cercospora kikuchii that affect soybean (Glycine max L. Merr.) worldwide and whose etiological agents are fungi classified in different species certain proximity. Objective. To provide an overview of the pathosystem of Cercospora Leaf blight and Purple Seed Stain caused by Cercospora kikuchii affecting soybean. Development. The degree of severity and/or incidence of both diseases varies in Argentina as well as in the rest of the world. Recent studies showed that there is great variability both morphologically and molecularly among C. kikuchii isolates obtained from petiole and seed in the northern, northern pampas, and southern pampas regions collected in the years 2015 and 2016. The chromosome-level genome of C. kikuchii is available. The genome assembly of 9 contigs is 34.44 Mb and the N50 is 4.19 Mb. Based on ab initio gene prediction, several pathogenicity-related candidate genes were identified, including 242 genes for putative effectors, 55 secondary metabolite gene clusters, and 399 carbohydrate-active enzyme genes. Conclusion. Cercospora Leaf Blight and Purple Seed Stain are endemic diseases in Argentina. The causal pathogen of both diseases shows great genetic and molecular variability in Argentina.